(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Biometric spoofing has huge implications in today’s world where everything from our smart phones to border control and airports require our fingerprints to authenticate our identity. In this quasi-experimental study, we have attempted to create artificial fingerprints with the help of 20 volunteers. We have then tested these artificial Biometric recognition refers to the automated recognition of individuals based on their anatomical and behavioral characteristics such as fingerprint, iris, face and voice. Biometric technology is now routinely used as security systems in mobile phones, to prevent fraud in banks, for border security, and even by various countries to provide a National ID card (Aadhar card in India). Systems protecting confidential data require strong security to ensure only the intended person can obtain access. Biometry provides a user-friendly way to achieve this. These biometric systems have the advantage of not requiring you to memorize a password or carry any identification documents¹. There are many types of biometric recognition systems based on modalities such as fingerprints, iris, face, voice, DNA, gait, etc. But amongst all of these, fingerprints were found to be the most suitable in terms of uniqueness, universality, permanency, collectability, acceptability and performance2. Hence, fingerprint recognition systems are currently the most popular biometric systems in use all over the world.